PANDUAN MELATIH BERPIKIR KRITIS DALAM MATA PELAJARAN PENDIDIKAN JASMANI, KESEHATAN DAN REKREASI (PJOK)SISWA SEKOLAH MENENGAH PERTAMA (SMP) DI KOTA PONTIANAK - Iskandar Iskandar; Hastiani Hastiani (Jurnal Pendidikan Olah Raga, 2022)
The purpose of this study was to train students' critical thinking skills in the Junior High School Physical Education subject in Pontianak City. The product research and development model that forms the basis of this research is the Dick & Carey instructional design model. The population in this study is students in the Physical Education and Health Subject at Junior High School in Pontianak City. The researcher's sampling technique to be used is total sampling. The data collection technique used is observation technique. The technique used to analyze the data in this study is descriptive qualitative. Based on the results of the first trial data recapitulation, the key score on the guidelines for the Game Performance Assessment Instrument (GPAI) Test/Basketball Game Performance obtained at this early stage obtained an average of 86 actions for each indicator, which means that effective performances often appear. This category means that students' critical thinking skills are quite good in terms of students' decisions in basketball playing material. In order to optimize students' critical thinking skills, interaction between educators and students is needed to reflect the behavior (effect) of teaching and learning under certain conditions. in the trial phase 2, the average action of each indicator has changed, based on the key score table, which means that effective performance always appears. This category means that students' critical thinking skills are optimal in terms of student support in basketball playing material. Based on the product developed through expert testing and field testing, the Guide to training critical thinking in the Physical Education subject for Junior High School Students (SMP) in Pontianak City is suitable for Physical Education learning.Â Â